Increasing power and taking a lead - What are practitioners really doing? Empirical evidence from Europeancommunications managers - Moreno, Ángeles; Verhoeven, Piet; Tench, Ralph; Zerfass, Ansgar (Instituto de Investigación en Relaciones Públicas, 2014)
The aims of the paper and presented research are to monitor trends in communication management and to evaluate specific topics that include decision-making style, leadership style, role enactment and the power of communication departments in Europe. This paper is based on data from the European Communication Monitor (ECM) annual research, the most comprehensive analysis of communication management worldwide. The ECM is an annual research project conducted since 2007. The ECM 2011 collected quantitative data through an on-line survey from 2,209 participating professionals from 43 European countries, with representation of every European region.This paper presents original connections about previous theory and offers empirical evidences about vertical and horizontal power of communication departments into organizations. On despite of the limitations of a self-reported survey, these evidences open new directions or research on hierarchical and social dimensions of power. The aim of this paper is to deepen the understanding of the power of communication management in organizations. Concretely, the paper aims to develop knowledge and understanding about horizontal and vertical power and the relationships established between these dimensions of power and strategic roles, decision-making and leadership styles that communicators play. The paper presents original ideas by critiquing and re-focussing the literature and theory of power and leadership in organizations. The paper also presents new empirical data to support these arguments.
Incrementar el poder y asumir el liderazgo - ¿Qué hacen realmente los profesionales? Evidencias empíricas sobre los gestores de comunicación en Europa
Keywords: Relaciones públicas; Comunicación en la empresa; Public relations; Power; Organizational Communication